Trends in the design of wavelength-based optical fibre biosensors (2008–2018) - Socorro-Leránoz, A.B.; Santano, D.; Del Villar, I.; Matias, I.R. (Biosensors and bioelectronics. X, 2019)
During the last decades, both governments and companies have been committed to the continuous checking of biological parameters, which can prevent extra costs to administrations. A very efficient way to address this issue is by designing biosensors. This contribution reviews the advances made using optical fibre technology, which have lately agglutinated much of the scientific interest related to the development of biosensors. However, the wide number of publications describing the use of optical fibre for detecting biomarkers has probably blurred the main goal: obtaining portable, simple, easy-to-handle and cost-effective biosensors. With this purpose, this contribution presents some optical fibre structures which have been analysed in terms of several optical parameters of interest from a photonics point of view: sensitivity, quality factor, full width at half minimum, limit of detection and figure of merit. This has made it possible to classify the most advanced optical fibre sensing techniques and, hence, their suitability when developing biosensing applications. •A thorough review on a hot topic in sensors field, fiber-optic biosensors, is offered.•The main optical platforms are compared on the basis of different parameters.•The relation between sensitivity, resolution and FOM with the LOD is discussed.•A ranking of optical platforms is given as a function of the different parameters.